ANGKA KONVEKSI TERMAL ALIRAN FLUIDISI PADA TABUNG HORISONTAL DAN ANGKA REYNOLDS RENDAH - Sontowiro, Pawito M (Mesin, 1998)
A ï¬uidized bed is a bed comprises a mixture of solid particles suspension in stream of gas. The heat transfer phenomenon between the surface of immersed body to/from ï¬uidized bed is very complicated mechanism. Aside from the governing variables on conventional convective heal transfer, the rate of heat transfer coefficient in ï¬uidized bed, is also inï¬uenced by physical and geometrical properties of solid particle. One of the variables which governs the value of thermal convective heat transfer coeï¬icient is voidage. The inï¬uence of voidage on thermal convective heat transfer coefficient at low Reynolds number will be reported on this paper.